(Re)defining ecolinguistics in Indonesia’s research: : A systematic review - Isti'anah, Arina; Suhandano, Suhandano (Politeknik Negeri Bali, 2023)
The emergence of ecolinguistics in the early 1970s has expanded into various academic discussions, including Indonesia’s context. Many articles of ecolinguistics can be found massively online, yet only few of them are stored in an international database, such as Scopus and DOAJ. This article attempts at (re)defining ecolinguistic concept in Indonesia’s research by taking 19 sample articles indexed in doaj.org. To collect the data, the researches searched the keywords “ecolinguistics” and “Indonesia” and applied the systematic review method by comparing the definition of ecolinguistics, its methods, and findings of ecolinguistic research in Indonesia. There are found some definitions of ecolinguistics: the study of language diversity, local wisdoms, language endangerment, and ecological awareness. Based on those findings, this article tries to redefine the concept of ecolinguistics as an approach that does not only take data from ecological issues, but also use ecological approach to analyze texts. By doing so, it is expected to figure out critical studies that find out ecological effects from the linguistic strands from various sources to offer more ecological understandings.